The outcome spectrum for Dilated Cardiomyopathy and Ventricular Tachycardia: results from the prospective, multicenter, DCM-VT ablation study. (19th May 2022) - Zeppenfeld, K; Wijnmaalen, AP; Ebert, M; Baldinger, SH; Vaseghi, M; De Riva Silva, M; Gaspar, T; Tedrow, U; Deneke, T; Soejima, K; Shivkumar, K; Carbucicchio, C; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Private company. Main funding source(s): The study was partially supported by an investigator initiated grant from Biosense Webster (a Johnson & Johnson company) Background: Recurrent sustained ventricular tachycardia (VT) due to nonischemic dilated cardiomyopathy (DCM) is difficult to treat and long-term outcome data are limited. Objective: We aimed to identify predictors for mortality or heart transplantation (MHT) and VT recurrence. Methods: Consecutive DCM patients accepted for VT catheter ablation (RFCA) in 9 centers were prospectively enrolled and followed. Results: Of 281 consecutive patients (age 60±13yrs, 85% men, LVEF 36±12%) 35% had VT storm, 20% incessant VT, and 68% failed amiodarone. During a median follow-up of 21 (IQR 6-30) months after RFCA (epicardial in 58%, no RFCA due to inaccessible target in 6.4%), 67(24%) patients died/underwent HT and 138(49%) had VT recurrence (45 within 30 days defined as early); the cumulative 4-year rate of VT or MHT was 70% and of MHT 38%. In multivariable analysis predictors of MHT were early VT recurrence (HR 2.92 (CI1.37-6.21), p<0.01), amiodarone at discharge (HR 3.23 (CI1.43-7.33, p<0.01), renal dysfunction (HR 1.92 (CI1.01-3.64), p=0.046), and LVEF (HR 1.36 (CI 1.0-1.84), p=0.052). A LVEF ≤32% was the optimal threshold to identify patients at risk for MHT (AUC 0.75). MHT per 100 person-years was 40.4 after early VT recurrence and significantly higher, compared to 14.2 after later VT recurrence and to 8.5 after RFCA with no VT recurrence (both p<0.01). Mortality rates for patients with VT recurrence after 30 days were not significantly higher than for patients with no VT recurrences Patients with early recurrence and LVEF≤32% had a 1-year MHT rate of 55% (figure). VT recurrence was predicted by prior ICD shocks, basal antero-septal VT origin, and procedural failure but not LVEF. Conclusion: DCM patients needing RFCA for VT are a high-risk group. Following RFCA half remain free of VT recurrences. Early VT recurrence with LVEF<0.32 identifies those with a very high risk and screening for mechanical support/ HT should be considered. Late VT recurrence after RFCA does not predict worse outcome.